Thermo-Responsive Shape Memory Thermoplastic Elastomer Based on Natural Rubber and Ethylene Octene Copolymer Blends - Ekwipoo Kalkornsurapranee; Adisak Keereerak; Nussana Lehman; Akarapong Tuljittraporn; Jobish Johns; Nattapon Uthaipan (Advances in Polymer Technology)
The shape memory (SM) polymers with superior SM properties were successfully fabricated based on melt blending of natural rubber (NR) and ethylene octene copolymer (EOC) at various crystallinity of EOC phase. The differential scanning calorimetry analysis, mechanical properties, temperature scanning stress relaxation, and shape memory properties were studied. Results revealed that the mechanical and thermal properties of the prepared NR/EOC blends improved as a function of amount of ethylene fraction in the EOC phase. The ethylene segment of EOC in the NR/EOC blend is triggered as a stimulus-sensitive domain. The shape memory properties in terms of shape fixity and shape recovery efficiencies of the blends tended to increase with the increasing of crystalline segments in the blends. The shape memory properties of the prepared blends substantially exceed the best performance (close to 100%) by blending the NR/EOC at 50/50 parts by weight, having 62%–80% of ethylene content in the EOC phase, which corresponds to approximately 3°–16° of crystallinity of EOC phase in the blends.